USE OF HEPATOPROTECTORS IN PATIENTS WITH OVARIAN CANCER - S. V. Tumanyan; N. D. Ushakova; D. V. Yartseva (Общая реаниматология)
Objective: to evaluate the efficiency of pharmacological correction of endogenous intoxication in patients with Stages III—IV ovarian cancer (OC) in the perioperative period. Subjects and methods. Thirty-to-70-year old seventy patients with Stages III-IV OC who had been surgically treated under general anesthesia were examined. The bio chemical parameters of intoxication, such as middleweight molecules, the total, effective concentration and binding capacity of albumin, integral hematological indices of intoxication, and C-reactive protein, were studied in the perioperative period. Results. Analysis of the performed tests showed that the premorbid background in all the examinees was characterized by varying degrees of endogenous intoxication (EI), increased leukocytic index of intoxication, hematological index of intoxication, and modified hematological index of intoxication, an imbalance between the accumulation and binding of overproduced toxic ligands, the intensified production of acutephase inflammatory proteins by the activation of a systemic inflammatory response, and decreased systemic responsiveness. These changes occur with suppressed systemic responsiveness, inadequate intoxication compensation by physiological detoxification systems and hemostatic instability. Conclusion. The use of heptral and Remaxol as part of the metabolic pharmacological correction infusion program nonequivalently caused reductions in the activity of an inflammatory response and the efficiency of EI correction in patients with OC in the perioperative period. The administration of Remaxol for systemic hyporesponsiveness and pronounced intoxication in OC patients promoted the optimization of systemic responsiveness, by producing a reduced toxic effect of tumorassociated EI.